Effects of reactivity metakaolin on properties of high strength concrete - Ahmed Aday, Luma (International Journal of Engineering and Technology, 2018)
Reactivity Metakaolin (MK) is an engineered pozzolanic mineral admixture, reacts aggressively with calcium hydroxide, which results in significant performance of concrete.In this work, different aspects of concrete mechanical behaviors have been studied including compressive and flexural strengths. In addition, some characteristics of concrete durability were investigated including absorption and porosity.In mixture proportioning, 5% and 10% of cement content is replaced by MK it was observed that concrete with 5% and 10% MK would perform almost the same in improving the mechanical properties of the materials. However In term of workability and durability, a better performance was obtained in concrete with MK. All mixes compressive strength is determined at 7 and 28 days. Current experimental study shows that 10% replacement of cement by Metakaolin gives higher strength.Â Â